Ethnic Minority Youths’ Encounters With Private Security Guards: Unwelcome in the City Space - Elsa Saarikkomäki; Anne Alvesalo-Kuusi (Sage Publications, 2022)
An increasing amount of literature is suggesting that ethnic minorities perceive their relations with the police as negative and procedurally unjust. There is, however, a distinctive lack of research on the relations between ethnic minorities and private security agents. This study uses the qualitative interviews of 30 ethnic minority youths living in Finland to explore their interactions with security guards. The findings suggest that perceptions of discrimination, suspicion, being moved on, and exclusion from city space were common. The study advances the theorizations of the changes in policing and procedural justice and incorporates these into the discussions on policing the city space. It argues that net-widening of policing means that city spaces are becoming more unwelcoming for ethnic minority youths in particular, limiting their opportunities to use city spaces.